Pinpointing the PRDM9-PRDM7 Gene Duplication Event During Primate Divergence - Heerschop, Sacha; Fagrouch, Zahra; Verschoor, Ernst J.; Zischler, Hans (Frontiers in Genetics, 2021)
Studies on PRDM9’s function in model systems and its evolution during vertebrate divergence continuously shed light on basic molecular mechanisms of hybrid sterility and its evolutionary consequences. However, information about PRDM9-homolog PRDM7, its origin being placed in the primate evolutionary tree, as well as information about the fast-evolving DNA-binding zinc finger array of strepsirrhine PRDM9 are scarce. We thus aimed to narrow down the date of the duplication event leading to the emergence of PRDM7 during primate evolution by comparing a representative primate sample of PRDM-orthologs and paralogs in phylogenetic tree reconstructions. To confirm our PRDM7 paralogization pattern, database-deposited sequences were used to test the presence/absence patterns to be expected from the timing of paralogization. We also extended an existing phylogenetic tree of haplorrhine PRDM9 zinc fingers with strepsirrhine counterparts. Inclusion of strepsirrhine zinc fingers completes the primate phylogeny of PRDM9 zinc fingers. Moreover, with strepsirrhine data included, the phylogeny of PRDM9 zinc fingers shows distinct clusters of strepsirrhine, tarsier, and anthropoid degenerated zinc fingers. Here, we show that PRDM7 emerged on the branch leading to the most recent common ancestor of catarrhines and its origin is, therefore, more recent than previously expected. A more detailed character evolutionary study hints towards PRDM7 possibly evolving differently in Cercopithecoidea as compared to Hominoidea. It lacks the first four exons in Old World monkeys, and in Papionini exon 10 is also missing. Dating the origin of PRDM7 is indispensable for further studies regarding why Hominoidea representatives need another putative histone methyltransferase in testis.